Inflammatory ocular events after inactivated COVID-19 vaccination. Issue 6 (30th November 2022) - Fei, Ping; Feng, Huazhang; Li, Jing; Liu, Miaomiao; Luo, Jia; Ye, Hongfei; Zhao, Peiquan
ABSTRACT: To report potential vaccine-induced inflammatory ocular adverse events following inactivated COVID-19 vaccination. Retrospective study of patients with uveitis and other ocular complications following inactivated coronavirus disease 2019 (COVID-19) vaccination at a tertiary referral center between May 2021 and August 2021. Data collection consisted of demographic and clinical data. The study included 8 eyes of 5 patients (4 females, 1 male), with a mean age of 37.2 ± 12.5 years (range 28–59 years). Mean time between vaccination and ocular complications onset was 13.2 ± 11.9 days (range 3–30 days), including two patients after the first dose of the vaccine and 3 patients after the second dose. The cases reported were three anterior uveitis, one herpetic keratitis and iridocyclitis, and one posterior uveitis. Patients received treatment with local and/or systemic steroids and all the patients had good visual outcomes. Ocular inflammatory events may occur after vaccination with possible gender preponderance. However, they are rare and manageable. Overall, the efficacy and safety of vaccination should be emphasized.